Students’ Perspectives on the Use of Drama in English Language Learning - Safura, Siti; Netta, Ayuna; Sucianda, Annisa (Universitas Nurul Jadid, 2025)
This study aimed to explore students’ perspectives on the use of drama in English language learning and to identify the challenges encountered during its implementation. Employing a qualitative research design, the study was carried out in the English Education Department at Universitas Muhammadiyah Aceh. Five students who had participated in drama-based English classes were purposively selected as participants. Data were gathered through interviews, classroom observations, and reflective journals. Thematic analysis was utilized to interpret the data. The results indicate that students generally view drama activities positively, highlighting their contribution to improving speaking proficiency, enhancing motivation, promoting active participation, and offering a contextual and enjoyable learning environment. Despite these benefits, several challenges were reported, including performance anxiety, insufficient rehearsal time, and difficulties in memorizing scripts. These issues were addressed through collaborative learning, peer discussions, extended practice, and self-reflection. The study concludes that drama-based learning is an effective pedagogical strategy for promoting communicative and meaningful English learning. Therefore, its integration into foreign language education, particularly in higher education is strongly encouraged.